2011
DOI: 10.1186/1556-276x-6-288
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and thermal boundary resistance of nanostructures

Abstract: We present a fabrication process of low-cost superlattices and simulations related with the heat dissipation on them. The influence of the interfacial roughness on the thermal conductivity of semiconductor/semiconductor superlattices was studied by equilibrium and non-equilibrium molecular dynamics and on the Kapitza resistance of superlattice's interfaces by equilibrium molecular dynamics. The non-equilibrium method was the tool used for the prediction of the Kapitza resistance for a binary semiconductor/meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…These observations are consistent with MD results concerning the cross-plane conductivity of superlattices with rough interfaces: for regularly patterned interfaces, the cross-plane conductivity is slightly greater than ideal superlattices 20 , and the boundary conductance is enhanced 38 . When the roughness is random, the cross-plane conductivity shows a small decrease as compared with planar interfaces 19,39 . The small amplitude of the reduction is related to the small proportion of energy carriers affected by the atomic roughness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with MD results concerning the cross-plane conductivity of superlattices with rough interfaces: for regularly patterned interfaces, the cross-plane conductivity is slightly greater than ideal superlattices 20 , and the boundary conductance is enhanced 38 . When the roughness is random, the cross-plane conductivity shows a small decrease as compared with planar interfaces 19,39 . The small amplitude of the reduction is related to the small proportion of energy carriers affected by the atomic roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Designing superlattices with rough interfaces has been recently achieved, opening an avenue for reducing the thermal conductivity in the direction perpendicular to the interfaces 19 . Again, the physical mechanisms at play in the heat transport properties of rough superlattices have not been elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulations have been performed recently to understand the physical mechanisms ruling the transport properties of superlattices (Landry et al, 2008, Termentzidis et al, 2009,2011a,2011b,2011c. In this contribution, we will discuss the influence of the interface roughness and of the superlattice period on the in-plane and the cross-plane thermal conductivities of Si/Ge superlattices using both the EMD and NEMD methods.…”
Section: Thermal Conductivity Predictions For Si/ge Superlattices Immentioning
confidence: 99%
“…Chen & Neagu 1997 solving the Boltzmann Transport Equation for specular and diffuse interfaces showed that depending on the superlattice period, the thermal conductivity might be influenced either by the diffuse interface scattering or by the scattering induced by the dislocations. The literature is rich in this subject and a series of articles appeared with a lot of experimental (Capinski et al 1999, Huxtable et al 2002, Lee et al 1997 or theoretical results using lattice dynamics method or Equilibrium (Volz 2000, Landry 2008, Termentzidis 2011b, Termentzidis 2011c) and Non-Equilibrium Molecular Dynamics method (Liang & Shi 2000, Chen 2004, Termentzidis 2009, Termentzidis 2010.…”
Section: Thermal Conductivity Predictions For Si/ge Superlattices Immentioning
confidence: 99%
“…conductivity is determined by using the Fourier's law. This method has been used widely for the study of the heat transfer in the nanoscale [3,4,5,6,7]. The equilibrium molecular dynamics has also been employed with success [8,9,4,6], but the comparison of the two methods is not in the scope of this article.…”
Section: Introductionmentioning
confidence: 99%